Influence of Elevated Temperatures on Resistance Against Phoma Stem Canker in Oilseed Rape - Noel, Katherine; Qi, Aiming; Gajula, Lakshmi Harika; Padley, Craig; Rietz, Steffen; Huang, Yong-Ju; Fitt, Bruce D. L.; Stotz, Henrik U. (Frontiers in Plant Science, 2022)
Cultivar resistance is an important tool in controlling pathogen-related diseases in agricultural crops. As temperatures increase due to global warming, temperature-resilient disease resistance will play an important role in crop protection. However, the mechanisms behind temperature-sensitivity of the disease resistance response are poorly understood in crop species and little is known about the effect of elevated temperatures on quantitative disease resistance. Here we investigated the effect of temperature increase on Brassica napus quantitative resistance against Leptosphaeria maculans. Field experiments and controlled environment inoculation assays were done to determine the influence of temperature on R gene-mediated and quantitative resistance against L. maculans; of specific interest was the impact of weather on the severity of phoma stem canker. Field experiments were run for three consecutive growing seasons at various sites in England and France using thirteen winter oilseed rape breeding lines and cultivars with or without R genes and/or quantitative resistance. Stem inoculation assays were done under controlled environment conditions with a subset of such cultivars, using avirulent and virulent L. maculans isolates, to determine if an increase in ambient temperature reduces the efficacy of the resistance. High maximum June temperatures were found to be related to phoma stem canker severity. This temperature effect was reduced in cultivars with quantitative resistance and no such correlation was found for the cultivar ES Astrid with only quantitative resistance but no R genes. However, in the controlled environment conditions, cv. ES Astrid had significantly lower amounts of necrotic tissue at 20°C than at 25°C. This suggests that, under a sustained temperature of 25°C, the efficacy of quantitative resistance is reduced. Findings from this study show that temperature-resilient quantitative resistance is currently available in some oilseed cultivars and that efficacy of quantitative resistance is maintained at increased temperature but not when these elevated temperatures are sustained for long periods of time.